Analysis of the Secondary Network Flow Distribution in Absorption Heat Exchange Unit. (2017) - Wang, Xiaoyin; Zhao, Xiling; Sun, Tao; Fu, Lin
Abstract: An absorption heat-exchanger consists of an absorption heat pump driven by hot water and a conventional water-water heat exchanger. The return water of the secondary network is divided into two units: one part is sent into the water-water heat exchanger, heated by the primary network, and the other is heated in the absorption heat pump. Finally, the water of the two parts is mixed and transmitted to the end consumers. The flow distribution of the secondary network will affect the return water temperature of the primary network. The flow proportion of the secondary network and primary network in the water-water heat exchanger is selected 1:1~2:1, according to the experience in practice. However, the actual operation effect may not be optimal. The flow distribution principle of the secondary network is proposed in this paper through simulation calculation. The optimal flow distribution principle is obtained by calculating the minimum value of the return water temperature of the primary network. The results provide the reference for the optimized design and operation of the ab-sorption heat exchanger.